Investigating the Potential of Bridging as a Strategy for Handling Barriers : Project site: Bodenvägen, Luleå - Fornander, Alexandra (Luleå tekniska universitet, Arkitektur och vatten, 2018)
The aim of this thesis is to clarify which potential a bridging structure has for handling the consequences created by a physical barrier. The following questions are posed: -Is bridging a suitable strategy for handling a physical barrier? -In what aspects do barriers counteract the development of a qualitative urban environment? -What potential does bridging have as a strategy for addressing these aspects? By studying literature, reference projects and the project site, a framework is set up for handling barriers in general and for the requirements of the specific project site. A design suggestion is made with the objective to address these needs. It uses a combination of the strategies presented in order to adress the consequences of the barrier: decreased intensity, connectivity and lack of pedestrian invitation. The thesis does not recommend bridging as a general solution, as it is complex and requires thorough analyses. However, the thesis argues that the strategy of bridging should not be rejected immidiately, since it has a potential of place-making. The strategy can provide for qualitative public space while offering a direct passage across a barrier. Denna avhandling avser att klargöra potentialen hos fysisk överbryggning som strategi för att hantera konsekvenserna av barriärer i stadsmiljö. Frågeställningarna är följande: -Är överbryggning en lämplig strategi vid hantering av fysiska barriärer? -Ur vilka aspekter motverkar barriärer utvecklingen av en kvalitetsmässigt god stadsmiljö? -Vilket potential har överbryggning som strategi för att adressera dessa aspekter? Genom att studera litteratur, referensprojekt och ett utvalt projektområde (Bodenvägen, Luleå) beskrivs ett ramverk för hur barriärer i allmänhet bör hanteras, samt vilka förändringar det specifika projektområdet behöver. Ett designförslag tas fram för att möta dessa behov. Det använder en kombination av strategier för att adressera konsekvenserna av barriären: minskad intensitet, minskad tillgänglighet samt brister i miljön för ...